Prevalence and associated factors of frailty among community dweller older adults living in Gondar town, northwest, Ethiopia: a community based cross-sectional study - Mihret Dejen Takele; Kedir Sany; Kefale Getie; Dechasa Imiru Wayessa; Gashaw Jember; Melese Gobezie; Yohannes Abich; Alemu Kassaw Kibret (BMC Public Health, 2023)
Abstract Background Frailty is a multidimensional geriatric condition that increases vulnerability to stressors, increases the risk of negative health outcomes, and lowers quality of life in older people. However, little attention has been paid to frailty in developing countries, particularly in Ethiopia. Therefore, the aim of the study was to investigate the prevalence of frailty syndrome and the sociodemographic, lifestyle, and clinical factors associated with it. Methods A community-based cross-sectional study design was conducted from April to June 2022. A total of 607 study participants were included using a single cluster sampling technique. The Tilburg frailty indicator, which is a self-reported schedule for assessment of frailty, required respondents to answer ‘yes’ or ‘no’ and the total attainable score ranged from 0 to 15. An individual with a score of ≥ 5 considered frail. Data were collected by interviewing the participants using a structured questionnaire, and the data collection tools were pre-tested before the actual data collection period to check for the accuracy of responses, language clarity, and appropriateness of the tools. Statistical analyses were performed using the binary logistic regression model. Results More than half of the study participants were male, and the median age of the study participants was 70, with an age range of 60–95 years. The prevalence of frailty was 39% (CI 95%, 35.51–43.1). In the final multivariate analysis model, the following factors associated with frailty were obtained: older age (AOR = 6.26 CI (3.41–11.48), presence of two or more comorbidities (AOR = 6.05 CI (3.51–10.43), activity of daily life dependency (AOR = 4.12 CI (2.49–6.80), and depression (AOR = 2.68 CI (1.55–4.63) were found to be significant factors. Conclusion and recommendations Our study provides epidemiological characteristics and the risk factors of frailty in the study area. Efforts to promote physical, psychological, and social health in older adults are a core objective of health policy, especially for older adults aged 80 and above years, and those with two or more comorbidities.